Students’ Needs Analysis of Business English At ESP Class For Business Administration Department At Nommensen HKBP University - Yensi Nurisa Simaremare; Erika Sinambela; Sondang Manik (Cetta: Jurnal Ilmu Pendidikan, 2023)
Nowadays, practically all job profession criteria demand job candidates to be proficient in the language of their preferred professional industry, particularly English. This research was conducted to examine the challenges faced by the Business Administration Department, specifically the second-semester students at Nommensen HKBP University, in using English and their need for Business English in ESP classes. It follows Hutchinson and Waters' theory, which consists of target situation needs and learning needs. Target situation needs include "necessities," "lacks," and "wants," while learning needs refer to how learners learn the language. The method used in this research is qualitative. Data was collected through a Semi-structured interview with the lecturer, as well as questionnaires given to the students via Google form.  In collecting and analyzing the data, the researcher followed Miles, Huberman, & Saldana's concepts are data collecting, data reduction, data display, and conclusion. The researcher also used some tables and charts to describe and calculate the data accurately. The result of this research showed that Business administration students struggle with English learning due to lack of vocabulary, mispronunciation, and incorrect sentence structure. These issues cause anxiety and hinder effective communication. To improve, students should learn to comprehend reports in curves or tables. On the other hand, Business Administration students need to master four English language skills: speaking, listening, reading, and writing. 96% prefer an English for Business class to understand its value in their professional field. Lessons should be weekly, small, and include oral presentations, group discussions, and writing.